Waste Generation and Community Behavior in Waste Management in Banjarbaru City in 2024 - Muhammad Pahruddin; Zulfikar Ali As; Abdul Haris (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2025)
Waste management has become a pressing environmental issue in Banjarbaru City, with increased waste generation due to population growth and economic activities. This study aims to provide a comprehensive picture of waste generation, composition, and community behavior in waste management. The research method was quantitative, with sampling based on the SNI 19-3964-1994 standard. Primary data was collected through a survey of 112 households and questionnaire-based interviews. Analysis was conducted using the chi-square test to identify the relationship between behavioral variables and waste generation. The results showed that the average daily waste generation reached 4.91 kg for wet and 2.80 kg for dry waste. Wet waste is dominated by organic waste, while dry waste comprises plastic and paper. An analysis of community behavior shows that only 20% of respondents actively separate organic and inorganic waste. Implementing programs such as waste banks helps reduce the burden on landfills, but infrastructure and community awareness challenges remain. Statistically, no significant relationship was found between community behavior in waste handling/management at the household level and the amount of waste generated, with p-values ranging from 0.099 to 1.000 (=5%). The conclusion of this study highlights the importance of collaboration between government, community, and technology to create effective and sustainable waste management